2007
DOI: 10.1002/adma.200701265
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Highly Regioregular Poly(3‐hexylselenophene) for Photovoltaic Applications

Abstract: Solar cells based on conjugated polymers are attracting increasing interest due to their potential to enable a renewable energy technology based on simple and low cost manufacture.[1] Devices made from blends of regioregular poly(3-hexylthiophene) (P3HT) and [6,6]-phenyl-C 61 -butyric acid methyl ester (PCBM) have been widely studied and are consistently reported to produce efficiencies over 3%. [2,3] Regioregular P3HT is known to be a good hole transporting polymer with relatively long wavelength absorption, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
143
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(153 citation statements)
references
References 16 publications
10
143
0
Order By: Relevance
“…For example, a recent report on poly(3-hexylselenophene) (P3HS) solar cells has shown that this materials has a better short-circuit current (due to better spectral response), yet poorer fill factor (due to poorer charge transport in a P3HS-electron acceptor blend) than (P3HT). [59] The result is a slightly decreased efficiency (2.7% for P3HS and 3.0% for P3HT) under analogous conditions. Researchers are cautioned not to draw conclusions about these polymers prematurely.…”
Section: Discussionmentioning
confidence: 95%
“…For example, a recent report on poly(3-hexylselenophene) (P3HS) solar cells has shown that this materials has a better short-circuit current (due to better spectral response), yet poorer fill factor (due to poorer charge transport in a P3HS-electron acceptor blend) than (P3HT). [59] The result is a slightly decreased efficiency (2.7% for P3HS and 3.0% for P3HT) under analogous conditions. Researchers are cautioned not to draw conclusions about these polymers prematurely.…”
Section: Discussionmentioning
confidence: 95%
“…[36] Their chemical structure is almost the same as that of rr-P3HT, but the sulfur atoms in the backbones are substituted by selenium atoms. It has been expected that the narrower band gap of rr-P3HS may lead to a more pronounced absorption in the BHJ device.…”
mentioning
confidence: 99%
“…The HOMO level of these polymers ranges from À4.8 eV (P3HT) to À5.9 eV (F8BT). [13][14][15] F 4 TCNQ is found to be dissolved in wide range of organic solvents including acetonitrile, toluene, chloroform, chlorobenzene, thiophene and xylene, to produce a concentration of 2 mg mL…”
mentioning
confidence: 99%